CONSTRUCTING THE MEANING OF DISEASE RECURRENCE: THE EXPERIENCE OF WOMEN WITH BREAST CANCER (Revista Latino-Americana de Enfermagem, 2001)
Regarding recurrence as a possibility in the lives of women with breast cancer, this work aimed at identifying how they construct the meaning of such possibility from their own existence. The study was based on the conceptions of symbolic interactionism and the content analysis of interviews with 12 mastectomized women was used. The possibility of recurrence was present in the lives of the women under study. It was configured by the uncertainty that they experienced and represented in the thematic units identified in their accounts when they stated to be "living with a stigmatizing disease", "experiencing a negative feeling" and "facing prejudice".